Relación entre el estrés académico y la ingesta alimentaria de los estudiantes del 1° y 3° año de Nutrición Humana de la Universidad Peruana Unión, 2011 - Moori Apolinario, Silvia Elida (2019)
Objective: To determine the relationship between academic stress with the power of the students of 1st and 3rdyear of Human Nutrition at the Universidad Peruana Unión 2011-1 cycle. Methodology: The study is descriptive,correlational, prospective, cross-sectional nonexperimental design. The instruments used are the Academic Stressinventory and the questionnaire of 24 hours recall. Results: The level of students’ academic stress of 1 and Year 3Human Nutrition address the different academic situations in the 2011 cycle is high, first year with an average of2.59, and for the third year with an average of 2.8 . Both values are considered high because the average exceeds 2.5.Students in both groups had a dietary intake of 1153.32 kcal on average, representing a 75.26% adequacy in relationto their caloric requirement, which on average is 1844.1 kcal. The decrease in food intake of students is related to thestress level in inverse proportion with correlation coefficient of -0.53 at a significance level of 0.01%. Conclusion:The study demostrate that there is an inversely proportional relationship. That is, the more levels of stress felt by thestudents surveyed had less food intake